British Columbia Native Indians: Distribution of Ethnic Groups - 1850 (text) (Government of British Columbia, 1956)
Commercial off-print of text accompanying map showing distribution of indigenous groups in British Columbia ca. 1850 (GOV-3; GOV-4).